Global Communication Program 2016 Year-End Presentation - Chen, Sibo (Stream: Interdisciplinary Journal of Communication, 2016)
The 3rd cohort of M.A. Double Degree Program in Global Communication are finishing their first year at SFU and will soon start the second year of study in Beijing. Prior to the departure, the students will present their capstone projects completed at SFU. The event will be hosted on Thursday, August 4 (9:00am to 4:00pm) at Harbour Centre, Room 7000. For more details, please see the attached PDF.